Exposure to Diisocyanates and Their Corresponding Diamines in Seven Different Workplaces. Issue 3 (14th February 2017) - Jones, Kate; Johnson, Paul D.; Baldwin, Peter E. J.; Coldwell, Matt; Cooke, Joan; Keen, Chris; Harding, Anne-Helen; Smith, Duncan; Cocker, John
Abstract: Biological monitoring to assess exposure to diisocyanates in the workplace is becoming increasingly widespread due to its relative ease of use and ability to look at all exposure routes. Currently, biological monitoring measures the corresponding isocyanate-derived diamine in urine, after hydrolysis. Because of this, any exposure to the diamines themselves released during the industrial process could confound the assessment of diisocyanate exposure. This paper reports an initial assessment of the extent of diamine formation and exposure during different processes involving diisocyanates including casting, grouting, core making, spray painting, foam blowing, and floor screeding. Air monitoring and glove analysis were conducted for both the relevant diisocyanate (measured as total NCO) and its corresponding diamine; urine samples were analysed (after hydrolysis) for the isocyanate-derived diamine. Processes that generated aerosols (as demonstrated by impinger analysis) such as spray painting and foam blowing were associated with the detection of diamines. Those processes that did not generate aerosols (casting, grouting, core making, and screeding) had no diamines detected, either in air or on gloves. In spray-painting tasks, diamines were a minor component (<15%) of the ambient concentration whereas in the foam blowing processes, where water is added to the process, diamine generation is more marked (up to eight times the airborne NCO concentration). Some non-aerosol processes gave rise to substantial diamine levels in urine (in exceedance of international guidance values, >5 µmol mol −1 creatinine) despite airborne levels being well within occupational exposure limits (20 µg m −3 total NCO in Great Britain); measurement data and statistical modelling indicated that skin absorption was the most likely exposure route. Foam blowing exposures were more complex, but urinary levels were greater than those expected from diisocyanate inhalation alone (measured as total NCO). This study provides evidence that biological monitoring for diisocyanates based on measuring the corresponding diamine in urine is valid, although any co-exposure to diamines themselves should be considered when interpreting results. It also demonstrates the potential for substantial skin absorption of diisocyanates in certain processes such as floor screeding and foam production.